Sistem Keadilan Pemilu dalam Penanganan Pelanggaran dan Sengketa Proses Pemilu Serentak 2019 di Sumatera Barat - Khairul Fahmi; Feri Amsari; Busya Azheri; Muhammad Ichsan Kabullah (The Constitutional Court of the Republic of Indonesia, 2020)
The electoral justice system has been established in Law Number 7 of 2017. It is marked the electoral justice system has been established in Law Number 7 of 2017. It is marked by the regulation of all procedures for implementing the election stages and the mechanism for handling election violations or disputes. The settlement of violations and election disputes is carried out by Election Supervisory Body (Bawaslu). In resolving violations and conflicts, Bawaslu has the authority to issue final decisions. With this authority, the role of Bawaslu is strengthened in the framework of law enforcement for election justice. This study would like to examine how this authority is exercised, especially in West Sumatra. West Sumatra has chosen because this province has become one of the most vulnerable areas in terms of organizing free and fair elections. Furthermore, there has also been an increase in the number of cases handled by Bawaslu in the 2019 elections compared to 2014 in West Sumatera. Therefore, how election law enforcement is carried out by Bawaslu to realize electoral justice, particularly in handling election violations and disputes. This article using normative legal research methods by relying on legal materials in the form of court decisions and decisions of the Bawaslu in province and city. In this study, it was concluded that the electoral justice system had implemented in the process of handling violations and disputes by Bawaslu in West Sumatra. All complaint report indicated it, i.e., administrative offenses, alleged criminal acts, and election disputes have been passed based on procedures determined by statutory regulations. However, there are still some weaknesses that must be evaluated because the election justice can not maximize.